“Betaone” barley water extract suppresses ovariectomy-induced osteoporosis in vivo and RANKL-induced osteoclast differentiation in vitro - Yongjin Lee; Hyun-Jin Lee; Kwang-Jin Kim; Han-Byeol Shin; Yoon-A Shin; Holim Jin; Ju Ri Ham; Soo-Young Choi; Mi-Ja Lee; Mi-Kyung Lee; Young-Jin Son (PLoS ONE, 2025)
Betaone is a variety of barley developed by the Korea Rural Development Administration. This study investigated the anti-osteoporosis effects of Betaone barley water extract (B1W) on ovariectomy (OVX)-induced bone loss in mice. To elucidate its mechanism, the effect of B1W on osteoclasts was assessed by measuring the protein expression of nuclear factor-activated T cells c1 (NFATc1), the expression of genes involved in osteoclast differentiation, and bone pit assays. B1W (300 mg/kg/day) significantly increased bone mineral density and bone volume fraction, but decreased trabecular separation compared to the OVX group. B1W also showed a trend towards decreasing serum C-telopeptide of collagen type 1 levels in OVX mice. Additionally, B1W reduced the expression of NFATc1 and downregulated the mRNA expression levels of various marker genes such as c-Fos, tartrate-resistant acid phosphatase (TRAP), cathepsin K (CTSK), dendritic cell-specific transmembrane protein (DC-STAMP), and osteoclast-associated Ig-like receptor (OSCAR). B1W reduced the osteoclast activity in the receptor activator of nuclear factor-κB ligand (RANKL)-treated osteoclasts by inhibiting the mitogen-activated protein kinase (MAPK) pathway. Based on the results, B1W can be considered a useful candidate for a therapeutic agent for treating conditions of bone loss and could also be used as an ingredient in health supplements.